Komparasi senyawa volatil dalam serai wangi secara proximate analysis - Ni Made Suaniti; I Wayan Bandem Adnyana; Manuntun Manurung (Department of Mechanical Engineering, University of Udayana, 2021)
Proximate as an initial analysis to detect the percentage of volatile compounds in citronella as an antioxidant and citronella waste can be made activated charcoal to purify waste such as used cooking oil. The purpose of this study was to compare the volatile compounds contained in citronella powder and charcoal. The analytical method used is Proximate Analysis. The lemongrass powder was put in an oven at 500oC for 24 hours to get charcoal. The test results showed that there was a decrease in the content of volatile compounds after making citronella charcoal by 46.88% in wet conditions and 61.02% in dry conditions. However, after citronella was added to virgin coconut oil (VCO) 10% w/w increased the volatile percentage to 100% for charcoal and 99.98% for powder with 0.9% moisture in both citronella.